Dissociation between two-dimensional and three-dimensional echocardiography – clinical implications. (3rd October 2022) - Lyng Lindgren, F; Bundgaard Ringgren, K; Ascanius Jacobsen, P; Tayal, B; Hay Kragholm, K; Holmark Andersen, N; Zaremba, T; Biering-Sorensen, T; Mogelvang, R; Schnohr, P; Boje Jensen, G; Sogaard, P
Abstract: Objectives: To investigate the agreement between two-dimensional (2DE) and three-dimensional echocardiography (3DE) in a general population, along with clinical impact of the differences. Background: Left ventricular ejection fraction (LVEF) has prognostic value and is used to guide cardiac treatment. The preferred technique is two-dimensional (2D) echo, although three-dimensional (3D) echo is more accurate when compared to MRI. Our study evaluates the agreement between 2D and 3D LVEF and the potential clinical impact of disagreements. Methods: Study population ware participants from the Copenhagen City Heart Study, who underwent 2DE and 3DE between 2011–2014. Means of difference (MD) were assessed in participant groups with a LVEF below 40%, 40–50%, and above 50%. Age-adjusted Cox proportional hazard ratios (HR) were calculated for all-cause mortality, major adverse cardiovascular event (MACE) and cardiac event of any kind. Results: In total 2554 participants from the Copenhagen City Heart Study were included. Median age was 58.3 (IQR: 44.2–69.8) years and 1137 (44.5%) were male. Mean LVEF in 2D was 56.6% (95% CI: 56.4–56.9%) and 52.0% (95% CI: 51.7–52.4%) in 3D, p<0.05. MD increased the further LVEF deteriorated: −14.9% (95% CI: −16.0 to −13.9%) (LVEF <40%), −9.3% (95% CI: −9.8 to −8.9%) (LVEF 40–50%) and −1.2% (95% CI: −1.6 to −0.9%) (LVEF ≥50%). 2DE overestimated the LVEF relative to 3D in 1824 (71.4%) instances. 3D LVEF <40% was associated with a HR for all-cause mortality of 2.58 (95% CI: 1.55–4.31, p<0.05), MACE: 1.90 (95% CI: 1.22–2.98, p<0.05) and cardiovascular event: 1.61 (95% CI: 1.04–2.48, p<0.05). HR for 2D LVEF <40% 0.84 (95% CI: 0.21–3.41, p=0.80) (all-cause), 3.12 (95% CI: 1.64–5.94, p<0.05) (MACE) and 2.68 (95% CI: 1.42–5.09, p<0.05) (cardiovascular event). Conclusion: With declining LVEF, 2D echo is prone to significantly overestimate LVEF and a 3D LVEF less than 40% is associated with excess all-cause mortality but less with MACE and cardiovascular events when compared to 2D LVEF. Funding Acknowledgement: Type of funding sources: None.